An exploration of the perspectives of elite Irish rowers on the role of the sports physiotherapist - Woods, A.; Woods, C, B. (Physical Therapy in Sport, 2012)
The purpose of this study was to (i) explore the perceptions of elite Irish rowers on the role of sports physiotherapy during their sports career, (ii) to compare their information to the International Federation of Sports Physiotherapists (IFSP) competencies and standards and (iii) to use the information gathered to highlight issues regarding quality of sports physiotherapy services, and how these services could be enhanced.